2018
DOI: 10.1111/ddg.13473
|View full text |Cite
|
Sign up to set email alerts
|

S2k guidelines for the use of topical preparations on the skin

Abstract: The present guidelines are aimed at dermatology residents and board-certified dermatologists as well as policymakers and insurance companies. Developed by dermatologists in collaboration with pharmacists using a formal consensus process (S2k), they include general aspects with respect to pharmacokinetics and regulatory terminology. Recommendations are provided on the various indications for extemporaneous preparations and their quality assurance. The importance of pharmaceutical vehicles and problems associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 36 publications
0
26
0
4
Order By: Relevance
“…The use of topical medication with anti-inflammatory agents is propagated in a phase-specific manner. This means that the choice of vehicle system and the active drug ingredient are selected and adjusted according to the disease activity in the therapeutic area [ 4 ]. This selection has a direct impact on the patient’s tolerability and adherence to topical therapy [ 5 ].…”
Section: Anti-inflammatory Topical Medicationmentioning
confidence: 99%
“…The use of topical medication with anti-inflammatory agents is propagated in a phase-specific manner. This means that the choice of vehicle system and the active drug ingredient are selected and adjusted according to the disease activity in the therapeutic area [ 4 ]. This selection has a direct impact on the patient’s tolerability and adherence to topical therapy [ 5 ].…”
Section: Anti-inflammatory Topical Medicationmentioning
confidence: 99%
“…1). 20 Some pharmacologically active substances may only be available in cosmetically 'unpleasant' vehicles for this reason. 20 Generally, the principles 'moist on moist' and 'greasy on dry' propose to use hydrating vehicles on acute lesions of hand eczema and lipid-rich vehicles on chronic ones.…”
Section: Topical Therapymentioning
confidence: 99%
“…Topical therapies should consider the appropriate choice of vehicles, suitable pharmaceutical vehicle depending on the condition of the skin and the acuteness of the eczema. 20 Generally, the principles 'moist on moist' and 'greasy on dry' propose to use hydrating vehicles on acute lesions of hand eczema and lipid-rich vehicles on chronic ones. This approach, however, is limited by the fact that patients may need to use their hands in everyday life not wishing to leave greasy marks on objects of their environment.…”
Section: Topical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous in vitro and ex vivo experiments revealed that Humulus lupulus (HL, hop) extract is a promising anti-psoriatic agent with prominent anti-proliferative effects [ 1 ]. Because epidermal barrier defects and scaling are pathogenetic key factors in psoriasis, the current guidelines and therapeutic concepts for psoriasis recommend a topical therapy with lipid-rich creams [ 2 ]. Similarly, other chronic inflammatory skin conditions with reduced lipid and ceramide content, such as atopic eczema, also benefit from a lipid-rich cream [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%